Analysis of Account Receivable Control to Minimize Uncollectible Receivable Risk at Novotel Bali Benoa Hotel & Resort - K A L Dewi; I W Karman; P Subiyanto (Journal of Applied Sciences in Accounting, Finance, and Tax, 2019)
The purpose of this research was to determine the credit policy at Novotel Bali Benoa Hotels & Resorts, to determine the performance of accounts receivable at Novotel Bali Benoa Hotels & Resorts and to find out how much the allowance for receivable losses should be established at Novotel Bali Benoa Hotels & Resorts. It uses a descriptive method for analyzing. Data used in this research are aging schedules, balance sheets, total credit sales, credit policy, and credit application forms. The analytical tool used in this research is 5C analysis to analyze the crediting standards, the credit policy used to analyze the compliance of receivables collection, the ratio related to accounts receivable and the allowance for receivable loss methods used to analyze the control of receivables. The results of this determination show that the credit policy implemented is not optimal because the hotel management does not pay attention to the 5C analysis in determining the prospective debtor and collecting bad debts. The performance of receivables measured by the ratio is not fulfilled maximum; this is attributed to the four sub-accounts held by only one sub-receivable that has good results. Allowance for losses from receivables that must be formed is IDR 509,663,985 in 2016, IDR 353,517,143 in 2017 and IDR 504,832,719 in 2018.